Molecular Basis of Plant Oil Biosynthesis: Insights Gained From Studying the WRINKLED1 Transcription Factor - Kong, Que; Yang, Yuzhou; Guo, Liang; Yuan, Ling; Ma, Wei (Frontiers in Plant Science, 2020)
Most plant species generate and store triacylglycerol (TAG) in their seeds, serving as a core supply of carbon and energy to support seedling development. Plant seed oils have a wide variety of applications, from being essential for human diets to serving as industrial renewable feedstock. WRINKLED1 (WRI1) transcription factor plays a central role in the transcriptional regulation of plant fatty acid biosynthesis. Since the discovery of Arabidopsis WRI1 gene (AtWRI1) in 2004, the function of WRI1 in plant oil biosynthesis has been studied intensively. In recent years, the identification of WRI1 co-regulators and deeper investigations of the structural features and molecular functions of WRI1 have advanced our understanding of the mechanism of the transcriptional regulation of plant oil biosynthesis. These advances also help pave the way for novel approaches that will better utilize WRI1 for bioengineering oil production in crops.